PENEGAKAN HUKUM CYBER CRIME DITINJAU DARI HUKUM POSITIF DAN HUKUM ISLAM - Jannah, H Sofwan; M. Naufal, M. (Al-Mawarid Jurnal Hukum Islam, 2012)
This articlewillexplainaboutcybercrime, effortsto overcome, focus, punishment andthe viewof Islami claw and positive law against cyber crime behavior. Cyber Crimeis a criminal activity using computer facilitiesor computer network without permission and against the law. According toIslamic shariathe punishment for cyber crime is taâzirby difference method, such as imprisonment, exile, whips, and death penalty. The punishment (taâzir) based on Islamic Law is very importance because Our country hasnât yet aspecial regulation governing cyber crime, exceptsomepositive law generally. Witha discussion of cyber crimein Islamic law, it became one of the alternatives and the way for controll ingthis criminal acts. Keywords:Cyber Crime, Hukum Positif, dan Hukum Islam.